1988
DOI: 10.1029/wr024i008p01308
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Birkenes Model of stream acidification using a multisignal calibration methodology

Abstract: A revision of the Birkenes model of streamwater acidification has been attempted to incorporate additional chemical and hydrologic information gained in the last 6 years since its original construction. The first stage of this effort has been an analysis of the hydrologic submodel with the goal of extending it to predict concentrations of a conservative tracer in streamwater. An objective calibration of the model indicated that the model is overparameterized. Only one passive store is identifiabile, not two as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
54
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(60 citation statements)
references
References 20 publications
5
54
1
Order By: Relevance
“…For example, Weiler et al [2003] identified different transfer functions for the two studied events examined related to distinct stormflow generating processes/sources; Iorgulescu et al [2005] identified a steep, almost threshold-like, increase in the soil water contribution with catchment wetness and similar shapes of the transfer function for the soil water and direct precipitation components. Another interesting inference from these studies is that multiresponse discharge and tracer data may support a higher-dimensional model parameterization than previously thought [e.g., Hooper et al, 1988].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…For example, Weiler et al [2003] identified different transfer functions for the two studied events examined related to distinct stormflow generating processes/sources; Iorgulescu et al [2005] identified a steep, almost threshold-like, increase in the soil water contribution with catchment wetness and similar shapes of the transfer function for the soil water and direct precipitation components. Another interesting inference from these studies is that multiresponse discharge and tracer data may support a higher-dimensional model parameterization than previously thought [e.g., Hooper et al, 1988].…”
Section: Introductionmentioning
confidence: 81%
“…Such water must be displaced from storage during the response to rainfall, implying that celerities associated with the propagation of the effects of the input are faster than the velocities of flow of that input. There is already an established literature demonstrating the use of tracer data response in the framework of conceptual catchment models [e.g., Hooper et al, 1988;Robson et al, 1992;Barnes and Bonnell, 1996;Kuczera and Mroczkowski, 1998;Uhlenbrook and Leibundgut, 2002]. More recently, Seibert and McDonnell [2002] adopted a flexible approach based on catchment-specific conceptual modeling using a set of interconnected boxes and ''soft'' data integration, though they assume that the effective mixing volumes for both runoff and tracer responses are the same.…”
Section: Introductionmentioning
confidence: 99%
“…Hooper et al [1988] developed and tested a multisignal optimization methodol-ogy of the Birkenes hydrochemical model in order to better assess the identifiability of the model parameters. They calibrated the model to runoff and tracer data and used simple and weighted least squares objective functions and a gradient search optimization technique in order to estimate model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…We view this use of isotopic data as one of the first formal attempts to include isotope-based hydrograph separation results into a model exercise. While a few studies in the past have used stream isotope concentrations through time for model calibration and testing [Hooper et al, 1988;Seibert et al, 2002a], there are no studies we are aware of that make use of computed new water ratios. O-18 time series could be used directly (i.e., as hard data), but often the observed signal is weak and observed time series are short and discontinuous (for review see Buttle [1994]).…”
Section: Utilization Of Soft Datamentioning
confidence: 99%
“…Few studies to date have used isotope data in model calibration-despite the now common use of this in watershed analysis ]. Hooper et al [1988] instance, snow cover information may be used. In cases where the expansion and contraction of surface-saturated areas is important (and considered in the model), knowledge of the maximal portion of the catchment that might become saturated can be used.…”
Section: Types Of Soft Datamentioning
confidence: 99%